On regional innovator networks as hubs for innovative ventures - Uwe Cantner; Tina Wolf (Friedrich Schiller University Jena, 2016)
At least since Schumpeter published his work "The Theory of Economic Development" (1912), a wide body of literature has focused on the evolutionary process behind firm growth and survival. Recently a growing interest is devoted to the variable "location" as a critical factor, shaping firm performance. However, less attention has been paid to the region-specific characteristics that may play a relevant role in determining the growth and survival of a firm. Some works see university-based knowledge spillovers as one such factor (Audretsch and Lehmann 2005, Cassia et al. 2009). This paper extends this approach to the regional innovator network, promoting region-specific knowledge spillovers. Two data bases are applied. First, patent data delivers the innovator network for Thuringia. The second data base contains firm specific information on innovative ventures founded in Thuringia in the period between 1990 and 2006. The results show that the firms individual probability to be innovative and connected to the innovator network positively influences the chances of this firm to survive.
Keywords: L26; D85; P25; O31; 330; innovation; entrepreneurship; networks; inventor; patents; survival